Fourier transform infrared investigation of non-heme Fe(III) and Fe(II) decomposition of artemisinin and of a simplified trioxane alcohol - Kapetanaki, Sofia M.; Varotsis, Constantinos (My University, 2001)
Fourier transform infrared spectra are reported for the Fe(III)- and Fe(II)-mediated activation of the antimalarial agents artemisinin I and its simplified synthetic analogue, trioxane alcohol 2. By monitoring the frequencies of the newly established marker lines in the FTIR spectra, the products of the Fe(II) and Fe(III) reactions have been characterized. In both reactions, artemisinin is activated giving a product mixture of a ring-contracted tetrahydrofuran acetatal 3, C4-hydroxy deoxyartemisinin 4, and deoxyartemisinin 5. These data illustrate that the oxidation state of the iron places no restrictions on the endoperoxide reduction mechanism. The FTIR difference (light - dark) spectra indicate that the endoperoxide moiety of artemisinin is photolabile and that the resulted products have the same vibrational characteristics as those observed in the reactions with Fe(II) and Fe(III). The use of 18O-18O enriched endoperoxide in 2 has allowed us to identify two oxygen sensitive modes in the reactions with Fe(II). The reduction of the peroxide bond by Fe(II) in trioxane alcohol 2 follows both the C - C cleavage and 1,5-H shift pathways and produces a ring-contracted tetrahydrofuran acetal 6 which is converted to tetrahydrofuran aldehyde 7 and C4-hydroxy deoxytrioxane alcohol 8, respectively. The cleavage of the O - O bond in 1 and 2 by iron and the ability to correlate vibrational properties of the reaction products with structural properties of the isolated products suggest that infrared spectroscopy is an appropriate tool to study the mode of action of antimalarial endoperoxides
Keywords: Alcohol; Fourier transform infrared spectroscopy; Artemisinin; Antimalarials; Derivatization; Electron transport; Pyrolysis; Lactones